The ethical hunter: how to consume animal life - Flygt, Adrian A., author; Rollin, Bernard E., advisor; Tucker, Dustin, committee member; Callahan, Gerald, committee member (Colorado State University. Libraries, 2013)
To view the abstract, please see the full text of the document.
Keywords: animal; killing; hunting; ethics